2006
DOI: 10.1021/la062536p
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Processes in Various Degrees of Dispersion

Abstract: While following voltammetric behavior of ultrafine metallic powders, we realized that the results obtained with six metals (Al, Fe, Ni, Cu, Mo, and W) were providing us with material for treating the connection between electroactivity and the state of dispersion of matter. The electroactive species were metallic oxides formed spontaneously on surfaces of the metallic powder particles, and we could follow their electrochemical reactivity in the states of coarse and fine suspensions, colloids, and true solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…As aqueous dispersion of pure aluminum hydroxide does not show that effect, with aluminum particles it is presumably due either to electroreduction of aluminum ions from some of the positively charged hydrolytic intermediates to aluminum atoms followed by their fast amalgamation and/ or to direct contact of the bared metallic core of the aluminum particles with mercury surface of the electrode. For the latter case are indicative occasional irregular flares of the current increase at negative potentials ( Figure 4, curve 1), typical for particulate mechanism of electron transfer [13 ]. Aluminum amalgam would immediately react chemically with the aqueous medium, unless it gets electrooxidized in a sufficiently fast potential scan (Figure 4).…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…As aqueous dispersion of pure aluminum hydroxide does not show that effect, with aluminum particles it is presumably due either to electroreduction of aluminum ions from some of the positively charged hydrolytic intermediates to aluminum atoms followed by their fast amalgamation and/ or to direct contact of the bared metallic core of the aluminum particles with mercury surface of the electrode. For the latter case are indicative occasional irregular flares of the current increase at negative potentials ( Figure 4, curve 1), typical for particulate mechanism of electron transfer [13 ]. Aluminum amalgam would immediately react chemically with the aqueous medium, unless it gets electrooxidized in a sufficiently fast potential scan (Figure 4).…”
Section: Full Papermentioning
confidence: 99%
“…Electrochemical behaviour of Al particles in aqueous medium is little known, therefore after some preliminary experiments with aluminum ultrafine particles, when we used voltammetry to generally characterize the degree of dispersion of several metallic powders [13], we now returned to Al powder to investigate the properties of its aqueous dispersions more thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…In our papers on the voltammetric behavior of ultrafine metallic powders [1][2][3] we have shown that different degrees of dispersion of electroactive species react at mercury electrodes in different characteristic ways. It is known that silver compounds can exist in aqueous media in various states of dispersion [4] and that they undergo complex mechanisms of particle formation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal solutions of these species already show some differences from true solutions, due to different sizes and related properties of individual particles; however, their transport to and from the electrode still occurs mostly by diffusion [10]. In fine suspensions the electroactive particles, of average dimensions between about 100 nm and 1 m, move in the medium by irregular Brownian motion and generate electrolytic current by particulate mechanism due to fortuitous impingements of the particles upon the electrode [1][2][3]. The "impingement" can be either direct mechanical contact of the electrode surface by the particle in a proper orientation, or an approach of the particle to the electrode within a distance over which electron tunneling can take place.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, methods of electrochemical characterization of micro-heterogeneous systems (e.g., sols) containing small particles, are not widely used. On testing electrochemical activity of ultrafine powders of six different metals, prepared by the method of electric explosion of wires [12], we found [13] that it is due primarily to electroreduction of surface layers of metallic oxides, formed spontaneously on the powder particles in course of their storage open to air. The electrochemical behavior of metal oxide layers on surfaces of highly dispersed metallic powders differs from that of individual metal oxide species in solutions [14].…”
Section: Introductionmentioning
confidence: 99%